2011
DOI: 10.1167/iovs.10-7043
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function Tests as Potential Biomarkers in Age-Related Macular Degeneration

Abstract: All the visual function tests had good diagnostic capacity. Combination of the 14-Hz flicker thresholds and dynamics of the PSR test provided optimal quantitative assessment of retinal function in early AMD, suggesting that this set is a potentially useful clinical tool for following progression of early AMD and assessing the efficacy of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 64 publications
9
139
0
1
Order By: Relevance
“…This model is on par with other medical assays. For example, photostress recovery evaluation was used to predict AMD with a 71% success rate (24), and optical coherence tomography was shown to detect the presence of AMD based on the presence of a prominent hyper-reflective haze present in the photoreceptor nuclear layer over drusen in 67% of patients with AMD (65). Small molecule biomarkers from the protein adduct class of compounds such as carboxyethylpyrrole were shown to discriminate between AMD and control plasma donors with ;76% accuracy (66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is on par with other medical assays. For example, photostress recovery evaluation was used to predict AMD with a 71% success rate (24), and optical coherence tomography was shown to detect the presence of AMD based on the presence of a prominent hyper-reflective haze present in the photoreceptor nuclear layer over drusen in 67% of patients with AMD (65). Small molecule biomarkers from the protein adduct class of compounds such as carboxyethylpyrrole were shown to discriminate between AMD and control plasma donors with ;76% accuracy (66).…”
Section: Discussionmentioning
confidence: 99%
“…Because an optimal therapeutic intervention would target early stages of disease, there is a great need for safe and effective ways to detect AMD early and safely monitor its progression. Decline in visual functions, particularly dark adaptation, becomes yet another potential biomarker in monitoring/predicting pathologies leading to AMD (22)(23)(24). Although development of a large number of animal models has helped to advance our understanding of retinal pathobiology and identify specific genetic factors that contribute to photoreceptor degeneration, inflammation, and the biochemistry of many retinal processes, these models all have limitations (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…54,55 More recently, Dimitrov and colleagues showed that while rod dark-adaptation rate had a better sensitivity (87%), a more clinically deployable combination of 14 Hz flicker threshold and photo-stress dynamic could detect 71% of early AMD cases and took 10-28 minutes. 56 De Kinkelder and colleagues found that early AMD subjects had a significantly lower hit rate than healthy controls in a rarebit test (detecting one or two very small light spots). 57 Wang and colleagues demonstrated that the ability to detect small bumps on an otherwise circular stimulus (shape discrimination) was significantly reduced in eyes with early AMD.…”
Section: Visual Function Testsmentioning
confidence: 99%
“…These include changes to contrast sensitivity [9][10][11], colour vision [12][13], flicker sensitivity [13][14], temporal thresholds [15][16][17], microperimetry [11,[18][19], photostress or glare recovery [11,[20][21][22] and dark adaptation [12][13][14][23][24][25][26]. When measured alongside these other visual functions, dark adaptation abnormalities have emerged as the most sensitive markers for early AMD [12][13][14]23].…”
Section: Introductionmentioning
confidence: 99%